Diversity of genetic platforms harboring the blaPER-2 gene in Enterobacterales and insights into the role of ISPa12 in its mobilization and dissemination - Ruggiero, Melina (2023)
The production of PER-like extended-spectrum β-lactamases has recently been associated with reduced susceptibility to the last resort drugs aztreonam/avibactam and cefiderocol. PER-2 has been mainly confined to Argentina and neighboring countries. Until now, only three plasmids harboring blaPER-2 genes have been characterized but very little is known about the involvement of different plasmid groups in its dissemination. The diversity of genetic platforms associated with blaPER-2 genes from a collection of PER-producing Enterobacterales was analysed by describing the close environment and the plasmid backbones. Full sequences of 11 plasmids were obtained by short read (Illumina) and long read (Oxford Nanopore or PacBio) sequencing technologies. De novo assemblies, annotation and sequence analysis were performed by Unicycler, Prokka and BLAST. Plasmid analysis revealed that the blaPER-2 gene is encoded on plasmids of different incompatibility groups (A, C, FIB, HI1B, N2), indicating that this gene may have been disseminated through a variety of plasmids. Comparison with the few publicly available nucleotide sequences describing the blaPER-2 genetic environment, including those from the environmental species Pararheinheimera spp. (considered as the progenitor of blaPER genes), indicates a role of ISPa12 in blaPER-2 gene mobilization from the chromosome of Pararheinheimera spp. Also, the blaPER-2 gene was carried by a novel ISPa12-composite transposon, Tn7390. In addition, its association with ISKox2-like elements in the close genetic environment in all plasmids analysed suggests a role of these insertion sequence elements in further dissemination of blaPER-2 genes.